Investigation of inhibition of human glucose 6-phosphate dehydrogenase by some 99mTc chelators by in silico and in vitro methods. (1st November 2016) - Şahin, Ali; Şentürk, Murat; Salmas, Ramin E.; Durdagi, Serdar; Ayan, Arif; Karagölge, Ali; Mestanoğlu, Mert
Abstract: The inhibitory effects of methoxyisobutylisonitrile (MIBI), diethylene triamine pentaacetic acid (DTPA), dimercaptosuccinic acid (DMSA) and metilendifosfonat (MDP) on human erythrocyte glucose 6-phosphate dehydrogenase (hG6PD) activity were investigated. For this purpose, hG6PD was initially purified 557-fold at a yield of 51.43% using 2′, 5′-adenosine diphosphate (ADP) sepharose 4B affinity gel chromatography. The in vitro effects of these chelators on hG6PD enzyme were studied. IC50 values of MIBI, DTPA, DMSA and MDP were 0.056, 0.172, 0.274 and 0.175 mM, of hG6PD, respectively. It was detected in in vitro studies that the hG6PD enzyme is inhibited due to these radiopharmaceutical chelators. In addition to in vitro studies, in order to better understand the molecular mechanism of studied compounds, combined in silico approaches, including molecular docking and molecular dynamics (MD), simulations were successfully performed. MD simulations shed light on inhibition mechanisms of the individual inhibitors into the ligand-binding pocket of hG6PD. Essential amino acids for binding are also investigated using per-residue interaction analysis studies.